Test Of the Effectiveness of Moringa (Moringa Oleifera) Leaves on The Number of Leukocytes and Platelets of Male Wistar White Rats (Rattus Norvegicus) Infected with Escherichia Coli - Sihombing, Jenny Ria; Napitupulu, Runggu Retno Justiani; Hendra, Hendra; Sipahutar, Nathalia Elizabeth Rouli; Sembiring, Indah Maharani; Sipayung, Yolanda Kresencia (International Journal of Membrane Science and Technology, 2023)
The research entitled Testing the Effectiveness of Moringa Leaves on the Number of Leukocytes and Platelets of Male Wistar White Rats infected with E.coli, used an experimental design with a Pre Test-Post Test Control Group Design. Where research carries out observations of the control and treatment groups before and after being given a treatment. The research used a purposive sampling technique. The subjects in this study were male white Wistar rats. The number of mice used was 27, which were divided into 3 groups. Data analysis used the Shapiro-Wilk test and One-way Anova test. The results showed that the average leukocyte count of white mice in the control group (K1) was 26.73x103/µL (pre test). Then after treatment (only standard feed) it was 22.98x103/µL (post test). In group (P1), the leukocyte count was 21.38x103/µL (pre test) and after administering the extract at a dose of 150 mg/KgBW/day, the leukocyte count was 16.03x103/?L (post test), for (P2) 20.63x103/µL (pre test ), after administering 250 mg/KgBW/day of extract, there was a decrease in the average number of white rat leukocytes and (P2) 13.72x103/µL (post test). The results of examination of the number of platelets (K1) infected with Escherichia coli bacteria and only given standard feed averaged 646.56x103/µL (pre test) and 954.103/ µL (post test). For group P1, the platelet count was 595.6x103/µL (pre test) and after administering Moringa leaf extract at a dose of 150 mg/KgBW/day, the platelet count was 858.8x103/µL (post test). For group P2, the platelet count was 637.1x103/ µL (pre test) and after administering Moringa leaf extract at a dose of 250 mg/KgBW/day 1029.2x103/ µL (post test). The results of the ANOVA test showed that there was a significant difference between the average leukocyte count and platelet count between the groups tested.